An anti-fouling poly(vinylidene fluoride) hybrid membrane blended with functionalized ZrO2 nanoparticles for efficient oil/water separation. Issue 9 (17th January 2017) - Shen, Xiang; Xie, Tiande; Wang, Jiangang; Liu, Peng; Wang, Fan
Abstract : Functionalized nanoparticle of ZrO2 grafted with poly( N -acryloylmorpholine) was synthesized via radical grafting polymerization. The nanoparticle was directly blended with PVDF to prepare hybrid membrane. The efficient separation of oil/water mixture is established. Abstract : Recent advances in the fabrication of organic–inorganic hybrid membranes have received a lot of attention in membrane technology for oily wastewater treatment. In this work, a hydrophilic PVDF hybrid membrane based on poly( N -acryloylmorpholine)-grafted ZrO2 nanoparticles (ZrO2 - g -PACMO), was prepared via a simple phase inversion method. PACMO was firstly grafted onto the ZrO2 nanoparticles via radical polymerization, avoiding the aggregation of ZrO2 - g -PACMO nanoparticles that was characterized by a sedimentation test. Then, the effects of the ZrO2 - g -PACMO nanoparticles on the structures and performances of resultant hybrid membranes were systematically investigated. The cross-section and surface morphology of the hybrid membranes were observed by field emission scanning electron microscopy and atomic force microscopy. The results indicated that the higher concentration of ZrO2 - g -PACMO nanoparticles in the casting solution led to a thicker sponge-like sub-layer and a rougher surface of hybrid membranes. The prepared PVDF/ZrO2 - g -PACMO hybrid membrane exhibited a lower amount of adsorbed protein than that of the pristine PVDF membrane. This behavior was revealed by pure water contact angle measurement and force–extension curves. It was also found from the oil/water filtration that the total fouling ( R t ) and irreversible fouling ( R ir ) were remarkably reduced, because of the higher hydrophilicity of hybrid membranes. Furthermore, the as-prepared membranes possessed also improved separation efficiency against oil/water mixtures and the rejection ratio was as high as 99.9%. Generally, a PVDF/ZrO2 - g -PACMO membrane may provide potential application for efficient oil/water separation.